A Common Genetic Influence on Human Intensity Ratings of Sugars and High-Potency Sweeteners. (17th July 2015) - Hwang, Liang-Dar; Zhu, Gu; Breslin, Paul A. S.; Reed, Danielle R.; Martin, Nicholas G.; Wright, Margaret J.
Abstract : The perception of sweetness varies among individuals but the sources of this variation are not fully understood. Here, in a sample of 1, 901 adolescent and young adults (53.8% female; 243 MZ and 452 DZ twin pairs, 511 unpaired individuals; mean age 16.2 ± 2.8, range 12–26 years), we studied the variation in the perception of sweetness intensity of two monosaccharides and two high-potency sweeteners: glucose, fructose, neohesperidine dihydrochalcone (NHDC), and aspartame. Perceived intensity for all sweeteners decreased with age (2–5% per year) and increased with the history of otitis media (6–9%). Males rated aspartame slightly stronger than females (7%). We found similar heritabilities for sugars (glucose: h 2 = 0.31, fructose: h 2 = 0.34) and high-potency sweeteners (NHDC: h 2 = 0.31, aspartame: h 2 = 0.30); all were in the modest range. Multivariate modeling showed that a common genetic factor accounted for >75% of the genetic variance in the four sweeteners, suggesting that individual differences in perceived sweet intensity, which are partly due to genetic factors, may be attributed to a single set of genes. This study provided evidence of the shared genetic pathways between the perception of sugars and high-potency sweeteners.